KONTRAK SEBAGAI KERANGKA DASAR DALAM KEGIATAN BISNIS DI INDONESIA - Ayu Pradnyani, Anak Agung; -, Marwanto (Kertha Negara : Journal Ilmu Hukum, 2013)
In business activities in Indonesia, the contract is a basic framework that is used as a frame of relations for economic actors. Principles of contract law are regulated in the Law-Civil Law. Contract may give rise to rights and obligations for the parties to make the contract. Thus the contract is very important in doing business in Indonesia.
Keywords: Role, Contract, Business